A case study of Northern Cyprus: The voice of senior academic administrators on education - Ulus Irkad; Bengi Sonyel; Hamit Caner (South African Journal of Education)
The purpose of the study reported on here was to introduce the perceptions of senior academic administrators in the Northern Cyprus Ministry of Education on the structure of the current education system as a whole. In order to carry out this case study, the views of 14 senior academic administrators were obtained through semi-structured interviews. There is no doubt that in qualitative research semi-structured interviewing is a flexible and powerful tool to capture the voices and the ways in which people make meaning of their experiences (Kvale, 2007). As Yin (2009:18) states: “An empirical inquiry about contemporary phenomena (e.g., ‘case’), set within its own real-world context – especially when the boundaries between phenomenon and context are not clearly evident.” Therefore, by reflecting on the current education system in Northern Cyprus as a case, we tried to show the real context of the education system itself. The data collected from the semi-structured interviews were analysed through content analysis. According to the findings of this research study, the current education system must be reconstructed considering the curriculum, strategies in teaching and learning approaches, developing of collaborative and student-centred classrooms, applying active learning strategies and voicing the voices of the senior academic administrators during the decision-making process.